Zorba the Buddha - Osho (New Delhi, 2013)
Zorba is not separate from Buddha. The West is not separate from the East. In fact, any materialism that has no values of spirituality is going to be very mundane, profane, ugly. It will not have any flights into the open sky towards the stars. It will not flower and release its fragrance, it will be just a rock. Spiritualism without materialism may have beautiful values but it is without foundations. It may create great palaces reaching to the stars but without foundations these palaces can only be hallucinations, they cannot be real. Zorba the Buddha is a selection made from Osho's discourses on the synthesis of materialism and spiritualism, the Zorba and the Buddha.
Keywords: Gurus